Modifikasi Permainan Softball di Sekolah Dasar - Waham Soetahir dan Agus Susworo Dwi Marhaendro (Jurnal Pendidikan Jasmani Indonesia, 2005)
This paper based on the understanding that sport must be introduced atearly stage in the childhood, in order to give better understanding about the philosophyof the game from the early stage.Softball for instance, it never been a popular sport. The reasons are the lackunderstanding about this sport, not to mention the gadget and equipment are expensiveto acquire. Indonesian people more accustomed to play a similar game called kasti.Student at elementary school played this game frequently.The writer wished to modify the softball and kasti games. This game will use the kastigadget and equipment but adapt the softball rule of play.Kata Kunci: Modifikasi, Permainan Kasti, Permainan Softball.